FGF23 Regulates Bone Mineralization in a 1, 25(OH)2D3 and Klotho‐Independent Manner. (29th August 2015) - Murali, Sathish Kumar; Roschger, Paul; Zeitz, Ute; Klaushofer, Klaus; Andrukhova, Olena; Erben, Reinhold G
ABSTRACT: Fibroblast growth factor‐23 (Fgf23) is a bone‐derived hormone, suppressing phosphate reabsorption and vitamin D hormone (1, 25(OH)2 D3 ) production in the kidney. It has long been an enigma why lack of Fgf23 or of Klotho, the coreceptor for Fgf23, leads to severe impairment in bone mineralization despite the presence of hypercalcemia and hyperphosphatemia. Using Fgf23 ‐/‐ or Klotho ‐/‐ mice together with compound mutant mice lacking both Fgf23 or Klotho and a functioning vitamin D receptor, we show that in Klotho ‐/‐ mice the mineralization defect is solely driven by 1, 25(OH)2 D3 ‐induced upregulation of the mineralization‐inhibiting molecules osteopontin and pyrophosphate in bone. In Fgf23 ‐/‐ mice, the mineralization defect has two components, a 1, 25(OH)2 D3 ‐driven component similar to Klotho ‐/‐ mice and a component driven by lack of Fgf23, causing additional accumulation of osteopontin. We found that FGF23 regulates osteopontin secretion indirectly by suppressing alkaline phosphatase transcription and phosphate production in osteoblastic cells, acting through FGF receptor‐3 in a Klotho‐independent manner. Hence, FGF23 secreted from osteocytes may form an autocrine/paracrine feedback loop for the local fine‐tuning of bone mineralization. © 2015 American Society for Bone and Mineral Research.